Encarceramento na penitenciária feminina de foz do iguaçu: como as detentas pensam e organizam a maternidade - Chaves, Karine Belmont (2023)
Imprisonment in Brazil is a critical issue and the data of the INFOPEN/ SISDEPEN show that the country is among the most incarcerated in the world. The male sex is predominant in the prison population and only in the twenty-first century women have achieved some visibility in prisons, due to periods of their expressive growth (according to official data), raising concerns in the intended penal treatment, about specific care, in relation to motherhood and their children, for example. Initially, projects of specific prison units were developed, later with space of coexistence for mothers and children and we found that public policies and the legal system also presented changes (with priority in guaranteeing the rights of the child), with the provision of application of alternative measures and penalties (for specific cases) so that women can be and take care of their small children, in their homes. This study, permeated by the sensitive reason of Michael Mafessoli, also had an exploratory and descriptive research, of a qualitative-quantitative nature. A questionnaire was applied to 188 women inmates in the Women's Penitentiary of Foz do Iguaçu – PR in the year 2021. Therefore, with the objective of analyzing how imprisoned women think and organize motherhood in their lives. The bibliographic research carried out initially surprised by the growth of studies on the subject. In various searches made, also in digital collections such as those of the platforms BDTD, CAPES e SCIELO, the state of the art surprised us, by the growth of works that address the theme, with the expressive presence of the area of health and social sciences. The structure of this thesis has 4 chapters, which cover the themes related to prison, crime, violence, psychology in prison, female incarceration and affective bonds (and we present prison as an affective border), motherhood and mothering. From all the discussion, from the reflections of authors such as Foucault, Goffman, Bauman and Winnicott, and from the interviews conducted, we found that motherhood is polysemic and they have different understandings of motherhood. Some are able to recognize their failures in mothering, in the (un)care of their children, due to their absence due also to prison. In general, they understand that being a mother involves affection, care and protection and they also understand that prison is not the best place for children's development. We found that the women prisoners organize themselves with the family support network available. Through the analyses, of so many life stories, we observed that many of them are marked by violence and conditions of vulnerability. Physical and mental health professionals, such as psychologists, are essential for the development of these people, also in prisons. The organization and structuring, personal and social, is fundamental for the full exercise of motherhood. Therefore, this thesis presents reflections, especially for the development of public policies. We are convinced that to think of women, inside and outside prison, and of their children, is to think of the relationships that are established between them and, broadly, of the values present in this culture and in these psychic constructions developed.